Bionic synthesis of a magnetic calcite skeletal structure through living foraminifera. Issue 9 (3rd June 2019) - Magnabosco, Giulia; Hauzer, Hagar; Fermani, Simona; Calvaresi, Matteo; Corticelli, Franco; Christian, Meganne; Albonetti, Cristiano; Morandi, Vittorio; Erez, Jonathan; Falini, Giuseppe
Abstract : This communication describes the bionic preparation of a composite material in which fluorescent magnetite nanoparticles are included within the calcitic skeletal structure of the foraminifer Amphistrigina lessoni . Abstract : This communication describes the bionic preparation of a composite material in which fluorescent magnetite nanoparticles are included within the calcitic skeletal structure of the foraminifer Amphistrigina lessoni . This research represents the first tailored experiment where a living calcifying organism is used to synthesize a CaCO3 composite, taking advantage of its control over the precipitation process, which has potentially no comparison with in vitro experiments.